2017
DOI: 10.1175/jcli-d-16-0529.1
|View full text |Cite
|
Sign up to set email alerts
|

Responses of the Summertime Subtropical Anticyclones to Global Warming

Abstract: Subtropical anticyclones dominate the subtropical ocean basins in summer. Using the multimodel output from phase 5 of the Coupled Model Intercomparison Project (CMIP5), the future changes of the subtropical anticyclones as a response to global warming are investigated, based on the changes in subsidence, low-level divergence, and rotational wind. The subtropical anticyclones over the North Pacific, South Atlantic, and south Indian Ocean are projected to become weaker, whereas the North Atlantic subtropical ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
70
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(80 citation statements)
references
References 50 publications
10
70
0
Order By: Relevance
“…Li, Li, and Kushnir () and Li et al () also reported westward shifts of the NASH from preindustrial conditions to the 21st century. He et al () reported strengthening of the NASH and weakening of the NPSH in CMIP5 models, and our results replicate this for both CMIP5 and CESM‐LENS, though in CMIP5 the spread is very large.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Li, Li, and Kushnir () and Li et al () also reported westward shifts of the NASH from preindustrial conditions to the 21st century. He et al () reported strengthening of the NASH and weakening of the NPSH in CMIP5 models, and our results replicate this for both CMIP5 and CESM‐LENS, though in CMIP5 the spread is very large.…”
Section: Resultssupporting
confidence: 93%
“…Changes in the positions and strengths of the subtropical highs are in fact anticipated as a result of global warming. Global climate model projections for the 21st century show a strengthening and westward shift of the North Atlantic subtropical high (NASH) with increasing greenhouse gas concentrations (He et al, ; Li et al, ; Li et al, ; Li et al, ), while projected trends in the North Pacific subtropical high (NPSH) are inconsistent across studies (He et al, ; Li, Li, Ting, & Liu, ). Variability in the NASH location has been linked to temperature and precipitation variability in the southeastern U.S. in observational data (Bishop et al, ; Katz et al, ; Li et al, ; Li, Li, & Kushnir, ), and changes in the strength of the subtropical highs can also impact precipitation in North America by changing winds and therefore moisture advection (Kushnir et al, ; Wei et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…These two studies only focused on the zonally asymmetric component of the NPSH and NASH. He et al () investigated the total response of the subtropical highs to global warming and found that the NPSH will weaken, while the NASH will strengthen in the future. To date, relative contributions of the zonal mean and zonally asymmetric components to the response of the NPSH and NASH to warming have not been carefully examined.…”
Section: Introductionmentioning
confidence: 99%
“…The position and intensity of WNPSH play a major role in the formation of the East Asia's climate by influencing the moisture transport from ocean and affecting the wind speed and temperature (He, Lin, et al, ). In the context of climate warming, many studies indicate that an enhanced WNPSH could lead to an enhanced southerly wind and a significant increase in the moisture transport (precipitation) over the high‐latitude areas of China in summer (He et al, ; He, Wu, et al, ; He & Zhou, ). The climate warming could lead to a weakened WNPSH and result in a weakened southerly wind and an increase in the cyclone weather over the low‐latitude areas in winter (Lin et al, ).…”
Section: Projection Of High‐resolution Climate Informationmentioning
confidence: 99%